Revisiting Fraud Theories in Indonesian Context: A Systematic and Critical Literature Analysis - Ida Kristiana; Nabila Syaharani Selima; Doddy Setiawan (Universitas Hayam Wuruk Perbanas, 2025)
Financial fraud, ranging from corporate mismanagement to embezzlement of public funds, remains a crucial issue in Indonesia, reflecting systemic weaknesses in governance and regulation. Utilizing theoretical frameworks, such as the fraud triangle, fraud diamond, fraud pentagon, and fraud hexagon, this study aims to explore various studies examining the factors contributing to financial fraud in Indonesia. This qualitative study uses the Charting the Field method to analyze 69 articles published in SINTA 2 and Scopus-indexed journals between 2016 and 2024. The results indicate inconsistencies in research findings due to methodological limitations, the use of incompatible dependent variables, and unrepresentative proxies for independent variables. There are gaps in author collaboration and thematic focus. Furthermore, some studies still focus on separate theoretical models. This study is expected to contribute to the accounting literature and serve as a reference for more innovative and contextually relevant further research.